VARIABILITY OF ROSMARINIC ACID, CARNOSIC ACID AND ANTIOXIDANT ACTIVITY IN THE SAGE COLLECTION OF THE GENEBANK IN GATERSLEBEN - Lamien-Meda, A.; Nell, N.; Lohwasser, U.; Börner, A.; Franz, C.; Novak, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Salvia officinalis L. (common sage) is a well-known medicinal plant with a variable essential oil composition, and an interesting anti-oxidative potential which is due predominantly to two main substances and their derivatives, rosmarinic and carnosic acid. In this study the rosmarinic acid, caffeic acid and some anti-oxidative parameters (total flavonoids, total phenolics, DPPH, FRAP) of 19 accessions of sage were evaluated in the sage collection of the genebank in Gatersleben (Germany). The aerial parts of 10 individual plants of each accession cultivated in 2006, were collected two times (2007 and 2008, from the same experimental field) at the beginning of the flowering period, and used for this study. The rosmarinic acid content was 6-46 mg/g in 2007 and 9-25 mg/g in 2008, and correlated well with all the other antioxidant parameters e.g. total flavonoid, total phenolics, DPPH (2,2-diphenyl-1-picrylhydrazyl ) and FRAP (Ferric reduction antioxidant power)antioxidant activities. The carnosic acid evaluated only with 2008 sample was varying from 0.5 to 4.3 mg/g and had low significant correlation with the antioxidant parameters. The results showed altogether the high potential of S. officinalis which is already in use as a natural antioxidant, due to its main phenolic compound, rosmarinic acid and carnosic acid. The present study showed a high variability between and also within accessions through the studied parameters, which could be exploited by plant breeders in sage genotype selection.